Use of modern geomatic techniques for creating and updating a green cadastre of urban trees and shrubs: a case study of Kumanovo city river bank - Mihajlovski, Bojan; Minchev, Ivan; Blinkov, Ivan; Simovski, Bojan (Ss. Cyril and Methodius University in Skopje, Faculty of Forestry in Skopje, 2018)
The goal of this paper is to implement modern, up-to-date, geomatics technique and technologies in the environment. The base is made in GIS software, a GPS device is used to record detailed points on the field and for recording and preparing a new orthophoto was used a modern sophisticated drone DJI Mavic Pro. QGIS (Quantum Geographic Information System), as a key software, was used for computer data processing and recordings obtained from the field research, and other utility programs were used to perform the tasks. The subject of the article is the Kumanovo city promenade in Macedonia, which is a convenient place to try and implement this data processing method. The results obtained give us a map of the entire urban dendroflora on the river bank in the city of Kumanovo. In fact, an inventory of all trees and shrubs was carried out, 4 projections were prepared with the help of modern applications, and as the ultimate goal, and a web digital map of the riverbank was prepared. This method can be applied in forestry, agriculture, water management, geodesy, space planning, sustainable development and environmental protection.
Original scientific article
Keywords: QGIS and GPS; drone; urban dendroflora inventory; geomatic techniques; remote sensing; Kumanovo